2010
DOI: 10.1590/s1415-47572010005000108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic damage induced by glyphosate isopropylamine salt using Tradescantia bioassays

Abstract: Glyphosate is noted for being non-toxic in fishes, birds and mammals (including humans). Nevertheless, the degree of genotoxicity is seriously controversial. In this work, various concentrations of a glyphosate isopropylamine salt were tested using two methods of genotoxicity assaying, viz., the pink mutation assay with Tradescantia (4430) and the comet assay with nuclei from staminal cells of the same plant. Staminal nuclei were studied in two different forms, namely nuclei from exposed plants, and nuclei exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…Taken together, these effects show that distinct differences exist in the sensitivity of cells from different organs and indicate that drug-metabolizing enzymes, which are represented in the enzyme activation mix and in HepG2 cells, increase the DNA-damaging properties of the herbicide. Also in different in vivo experiments, positive results were obtained in SCGE experiments, for example in amphibians (Clements et al 1997), reptiles (Poletta et al 2009), fish (Cavas and Konen 2007;Guilherme et al 2010), and plants (Alvarez-Moya et al 2011). Few years ago, the first article was published by Paz-y-Miño et al (2007) in which a significant increase of comet formation in peripheral lymphocytes of humans exposed to G via spraying was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these effects show that distinct differences exist in the sensitivity of cells from different organs and indicate that drug-metabolizing enzymes, which are represented in the enzyme activation mix and in HepG2 cells, increase the DNA-damaging properties of the herbicide. Also in different in vivo experiments, positive results were obtained in SCGE experiments, for example in amphibians (Clements et al 1997), reptiles (Poletta et al 2009), fish (Cavas and Konen 2007;Guilherme et al 2010), and plants (Alvarez-Moya et al 2011). Few years ago, the first article was published by Paz-y-Miño et al (2007) in which a significant increase of comet formation in peripheral lymphocytes of humans exposed to G via spraying was reported.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Table 7, two subsequent publications reported positive Comet results for glyphosate on Tradescantia flowers and nuclei (Alvarez-Moya et al, 2011) and negative Comet results for oyster sperm cells exposed to glyphosate (Akcha et al, 2012). The latter study employed a very low maximum exposure of 5 mg/L (&0.03 mM).…”
Section: Glyphosate and Glyphosate Saltsmentioning
confidence: 93%
“…55-18-5) being used as a positive control. These concentrations were used in a previous investigation (Alvarez et al , 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The risk of genotoxicity in humans is low in areas where glyphosate is applied for coca and poppy eradication (Bolognesi et al , 2009), but an association with multiple myeloma has been suggested (De Roos et al , 2005). In contrast, several studies using different tests have reported high genotoxicity for glyphosate (Sivikova and Dianovsky, 2006; Sparling et al , 2006; Cavas and Könen, 2007; Alvarez et al , 2011; Guilherme et al , 2012), with the genotoxicity observed being related to the test system used (Zñiga, 2001), e.g. , plants (Dimitrov et al , 2006; Alvarez et al , 2011; Truta et al , 2011), fish (Cavas and Könen, 2007) and human cells (De Roos et al , 2005; Bolognesi et al , 2009) are reportedly very sensitive to glyphosate.…”
Section: Introductionmentioning
confidence: 96%